Provincialising nature : multidisciplinary approaches to the politics of the environment in Latin America - Coletta, Michela; Raftopoulos, Malayna (Institute of Latin American Studies, 2016)
Provincialising Nature: Multidisciplinary Approaches to the Politics of the Environment in Latin America offers a timely analysis of some of the crucial challenges, contradictions and promises within current environmental discourses and practices in the region. This book shows both challenging scenarios and original perspectives that have emerged in Latin America in relation to the globally urgent issues of climate change and the environmental crisis. Two interconnected analytical frameworks guide the discussions in the book: the relationship between nature, knowledge and identity and their role in understanding recent and current practices of climate change and environmental policy. The different chapters in this volume contribute to this debate by offering multidisciplinary perspectives on particular aspects of these two frameworks and through a multidirectional outlook that links the local, national, regional and transnational levels of inquiry across a diverse geographical spectrum.